The Efficacy of Using a Rapid Diagnostic Test in Active Cases Finding of COVID-19 Infection in Community by Public Health Workers - Tongnoon, Sirapa; แสงแก้ว, แสงแก้ว (Journal of Primary Care and Family Medicine (PCFM), 2024)
Background and Objectives: The efficacy of Rapid Diagnostic Tests (RDTs) in diagnosing COVID-19 through active case finding depends on several factors, including the skill of specimen collection, test performance, and interpretation of results. This study assessed the efficacy of RDTs in diagnosing COVID-19 in active cases finding in a community-based practice by public health workers who received appropriate training. Design: A retrospective cross-sectional study Methods: This retrospective cross-sectional study was conducted at a temporary active case finding site in a community on August 10, 2021. Public health workers trained with a three-hour session including hands-on practice performed RDTs under the supervision of trained medical doctors. The testing was done by the public health workers from preparing RDTs to interpreting the test results. RDTs’ efficacy was compared with RT-PCR results performed in the same visit. Results: Out of 163 participants who had close contact with COVID-19 patients, 26 participants (16% of the total samples) had positive RT-PCR results. The testing showed a sensitivity of 88% (95% confidence interval 77% to 100%) and a specificity of 100% (100% to 100%). Subgroup analysis based on the presence of symptoms revealed no significant difference in the sensitivity and specificity of both groups. The sensitivity of RDTs in the symptomatic group was 86% (57% to 100%), and 89% (74% to 100%) in the asymptomatic group. Furthermore, the average cycle-time value of RT-PCR testing was above 30 for the samples that tested negative with the RDT. Conclusions: Using RDTs for active case findings of COVID-19 by public health workers was found to be comparably effective to RT-PCR testing during the pandemic while being less time-consuming and labor-intensive. Additionally, public health workers with limited experience in nasal swabbing and RDTs can be trained to effectively use these tools and help increase access to care and promote timely disease control.